RANCANG BANGUN ALAT PENYUSUN RAK PENJEMURAN DIATAS PARA- PARA KE DALAM BOKS SECARA SEMI MEKANIS - Hendra Saputra; Tamrin -; Muhamad Zen Kadir (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
Drying process by using Para-para is more effective than the conventional one which uses floor surface or plastic(terpal). The products will dried faster and cleaner, nevertheless the system tomoveand to arrange the finalproductis wastes a lot of time and energy. Hence, the objective of this reasech was to make a semi-mechanicalPara-para drying shelf that integratedly connect to semi machanic box in order to save time and energy uses. Thissemi-mechanical drying device contained of two frames, four shelves, two ropes,two box movement holdings,boxes, spring, big pulley and small pulley. The process started bywaiving its hook from the shelves thus the treadlewould pull the other connected components to the shelves and automatically move to the box. The pulleys wereused to set the shelves movements to the boxes, consequently the box will consecutively move to next lowershelflevel after being filled Furthermore, filled boxes caused an increasing of tensile strength which also increasethe speed of box movement. Box retention rate was used to decrease the fourth shelf speed that will prevent loss.The device were tested by dryingcassava and soybean. Finally, the result showed that it only consume 1,19seconds to move and arrange the product with less manpower assistance. Moreover, Para-para were succesfullysave time and manpower compared to manual movement which only take approximately 11,83 seconds for eachshelf.Keywords: Drying, semi-mechanic drying shelf, Para-para.